Beyond Primitivism : Indigenous Religious Traditions and Modernity. - Olupona, Jacob K. (Routledge, 2003)
At a time when local traditions across the world are forcibly colliding with global culture, Beyond Primitivism explores the future of indigenous religions as they encounter modernity and globalisation.